Accidents features in construction - Pichugin, Sergiy; Klochko, Lina (Academic journal Industrial Machine Building Civil Engineering, 2019)
This work aims to highlight the problem of accidents in the construction industry. On the basis of collected and processed information the accidents classification in the building is presented, depending on the building erection stage. The article gives a detailed description and analysis of such cases in the construction. The collection of information on accidents was carried out using various information sources: Internet resources, literary sources, scientific works and information from world-wide journalistic services. The findings are presented over the last ten years and cover worldwide construction incidents. The material is systematized and presented in the table form. The study results are the created accidents classification with the probability of their occurrence, which can be used later in the design of buildings and structures, in order to predict the various types of accidents in the construction.